Liberty and property: a social history of Western political thought from the Renaissance to Enlightenment - Meiksins Wood, Ellen (London, 2012)
"The formation of the modern state, the rise of capitalism, the Renaissance and Reformation, the scientific revolution and the Age of Enlightenment have all been attributed to the “early modern” period. Nearly everything about its history remains controversial, but one thing is certain: it left a rich and provocative legacy of political ideas unmatched in Western history. The concepts of liberty, equality, property, human rights and revolution born in those turbulent centuries continue to shape, and to limit, political discourse today. Assessing the work and background of figures such as Machiavelli, Luther, Calvin, Spinoza, the Levellers, Hobbes, Locke and Rousseau, Ellen Wood vividly explores the ideas of the canonical thinkers, not as philosophical abstractions but as passionately engaged responses to the social conflicts of their day."